Strategi Mengatasi Rendahnya Motivasi dan Partisipasi Belajar Siswa dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti - Tohet, Moch.; Mughis Ramadani, Ahmad; Mahbubi, M. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to identify and analyze effective learning strategies to increase student motivation and participation in Islamic Religious Education and Character Building (PAIBP) at Darul Hikmah Paiton Vocational School. This study used a qualitative approach with a case study method. Data collection techniques included observation, in-depth interviews, and documentation analysis. The results indicate that the implementation of active learning strategies such as group discussions, case studies, and the use of varied learning media significantly increased student engagement. The connection between the teaching material and students' daily life experiences, as well as the relational approach between teachers and students, are key factors in building learning motivation. This study recommends that PAIBP teachers implement a more contextual and participatory learning approach to create an inclusive and meaningful learning environment.